What's Up in Whatsapp Classroom: Exploring Students’ Perception in Learning Speaking Through Whatsapp during Covid-19 Pandemic - Soni Ariawan; Hery Rahmat; Kasyfur Rahman (Siliwangi University, 2021)
The present study attempted to find out students’ perception and challenges in learning speaking through WhatsApp which was designed with quantitative-descriptive approach in the form of online survey study. The survey was distributed to 51 EFL students at State Islamic University of Mataram. The students’ responses were coded and displayed descriptively into two main themes: students’ perception and students’ challenges. It was found that most of the students, 33 students or 64.7%, perceived WhatsApp as an effective learning platform because it could improve their speaking skill due to its usefulness and ease of use. However, there were 10 students or 19.6% of the students who claimed that WhatsApp was not an effective tool because it was not equipped with more practical features. The students also found it difficult to understand teachers’ explanation through WhatsApp. Another perception is neutral because the students believed that WhatsApp had both advantages and drawbacks. There were 8 students or 15.7% of them perceiving this. Even though the majority of the students showed positive attitude toward WhatsApp-based learning, they agreed to say that they experienced technical, practical and mental challenges during the learning. These challenges need to be anticipated by the teachers and students toward an effective online learning through WhatsApp. Keywords : WhatsApp classroom, technical problems, practical problems, mental problems